Building operation and maintenance in building information modelling (BIM) - Che Ku Muhammad Amirul Syafiq, Che Ku Pauzi (2018)
The management of information throughout a building's lifecycle is becoming increasingly important and building information modelling (BIM) is often used to ensure the interoperability of data. However, BIM based facility information from the construction phase is difficult to access and use during the operation and maintenance phase. This occurs because the BIM information is not utilized well in facility management (FM). In this research, we propose an approach to effectively manage BIM based FM information by linking the BIM based building elements and FM work information in an FM system database. We present the data FM information system that semantically links BIM data to relevant historical work records. The proposed ontology was evaluated using a sample dataset of the architectural maintenance work records of an office building. Using the proposed approach, facility managers will be able to increase their efficiency in searching related work records that consider shared BIM objects by enhancing the interoperability and accessibility of FM data.